The Analysis of Published Papers written by the Lecturer of the Faculty of Sport and Physical Education in Sport Mont from 2010 to 2012 - Ivan Vukovic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2020)
Sport Mont is an electronic and printed scientific journal that has been created in 2003 and it has been developed by Montenegrin Sport Academy. Main purpose of this journal is to represent people, the new scientific researches from sport science and medicine. This journal has been publishing 3 times per year, in February, June and October from the 2003 until nowadays. It has been published more than 1400 papers. Right now, Sport Mont is indexed in 23 scientific bases, in which the most popular are Scopus and Web of Science. In this paper, it has been made a systematic review of papers published by the lectures from Faculty from sport and physical education from Niksic in a period from 2010 to 2012. It has been founded 60 papers that were researching an amount of different areas of sport science. The results have showed that the lectures from the Faculty of Sport and Physical Education had the most interest in the area of sport training and from that area it has been founded 28 papers. When we talk about lectures that were publishing in that period, professor Dusko Bjelica has published 18 papers meaning that he has been the one who has published the most. At the end we can tell that the lectures from this faculty became very beneficent for this journal, which it shows their professionality and effort. Also, by putting this journal on the top of the area of sport science and promoting science in general in Montenegro.